Aggressive Behaviors and Depression: What are the linked? A Case Study among Drug Abuser - Lukman@Zawawi, Mohamad; Syafiq, M.S; Nurun Saadah, S (2018)
Research about depression and aggressive behavior always in hot debate. Among drug abuser, the connection is still controversial. Hence, it is important to study the relationship between depression and aggressive behavior as well as the most contributing factor of aggressive behavior caused by depression. This is a quantitative method in which using a survey to complete the study. Data were collected from 200 drug abusers in east coast prison in Malaysia. As a result, the connection between depression and aggressive behavior was high and the most contributing factor was physical aggression. Hence, it is crucial to the prison to take a proactive action to cure the mental health illness or drug abuser.